2011
DOI: 10.1073/pnas.1101478108
|View full text |Cite
|
Sign up to set email alerts
|

A yeast-based assay identifies drugs active against human mitochondrial disorders

Abstract: Due to the lack of relevant animal models, development of effective treatments for human mitochondrial diseases has been limited. Here we establish a rapid, yeast-based assay to screen for drugs active against human inherited mitochondrial diseases affecting ATP synthase, in particular NARP (neuropathy, ataxia, and retinitis pigmentosa) syndrome. This method is based on the conservation of mitochondrial function from yeast to human, on the unique ability of yeast to survive without production of ATP by oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 45 publications
2
87
0
5
Order By: Relevance
“…A strong F 1 defect like the one observed in the nM strain normally leads to low contents in complexes III and IV (Couplan et al, 2011), which is believed to reflect a regulatory mechanism that balances the expression of ATP synthase and respiratory enzymes. In one such mutant (fmc1D), we found that most of the nuclear-encoded subunits of these complexes are poorly expressed (Couplan et al, 2011).…”
Section: Molecular Cellmentioning
confidence: 99%
“…A strong F 1 defect like the one observed in the nM strain normally leads to low contents in complexes III and IV (Couplan et al, 2011), which is believed to reflect a regulatory mechanism that balances the expression of ATP synthase and respiratory enzymes. In one such mutant (fmc1D), we found that most of the nuclear-encoded subunits of these complexes are poorly expressed (Couplan et al, 2011).…”
Section: Molecular Cellmentioning
confidence: 99%
“…(Figure 2). De façon remarquable, ces deux molécules sont également actives de façon dépendante de la dose et à des concentrations de l'ordre de quelques dizaines à centaines de nM, validant ainsi définitivement nos modèles de levures NARP [13]. Par ailleurs, ces modèles nous ont permis d'isoler des composés actifs spécifiquement sur les phénotypes associés à certaines mutations NARP, ouvrant ainsi la possibilité de rechercher des pistes thérapeutiques personnalisées.…”
Section: Revuesunclassified
“…Enfin, des approches de chémogénomique ont été entreprises chez la levure afin d'identifier les voies cellulaires ciblées par ces molécules, une information cruciale pour leur optimisation, mais aussi pour mieux comprendre les processus physiopathologiques impliqués dans ces maladies très complexes et hétérogènes. Comme d'aucuns pouvaient s'y attendre, les voies identifiées (complexe III et import mitochondrial) sont conservées de la levure à l'homme, dévoilant ainsi de nouvelles pistes thérapeutiques potentielles pour traiter des maladies mitochondriales [13,14].…”
Section: Revuesunclassified
“…These data (Bach et al 2003(Bach et al , 2006Couplan et al 2011) show that for some processes, the conservation between yeast and the target organism is close enough to allow direct, informative screening against the model system. In addition, it is important to recognize that in all these cases of phenotypic rescue the possibility of generically toxic false positives is removed greatly simplifying the generation and interpretation of data.…”
Section: Y E a S T A S A L E T H A L E X P R E S S I O N P L A T F O R Mmentioning
confidence: 99%
“…This relates to a defect in the ATP synthase assembly and as such serves as an effective model for certain mitochondrial diseases e.g. NARP (neuropathy, ataxia and retinitis pigmentosa) (Couplan et al 2011). In their assay platform Couplan and colleagues used filters spotted with each compound to identify those that induced an enhanced halo of growth when placed on solid glycerol medium spread with the yeast strain of interest.…”
Section: Y E a S T A S A L E T H A L E X P R E S S I O N P L A T F O R Mmentioning
confidence: 99%